Development of thermal energy storage materials for biomedical applications. (September 2015) - Shukla, A.; Sharma, Atul; Shukla, Manjari; Chen, C. R.
Abstract The phase change materials (PCMs) have been utilized widely for solar thermal energy storage (TES) devices. The quality of these materials to remain at a particular temperature during solid–liquid, liquid–solid phase transition can also be utilized for many biomedical applications as well and has been explored in recent past already. This study reports some novel PCMs developed by them, along with some existing PCMs, to be used for such biomedical applications. Interestingly, it was observed that the heating/cooling properties of these PCMs enhance the quality of a variety of biomedical applications with many advantages (non-electric, no risk of electric shock, easy to handle, easy to recharge thermally, long life, cheap and easily available, reusable) over existing applications. Results of the present study are quite interesting and exciting, opening a plethora of opportunities for more work on the subject, which require overlapping expertise of material scientists, biochemists and medical experts for broader social benefits.